USE OF COMPUTER MATHEMATICAL PRACTICAL PACKAGES IN INCREASING THE EFFICIENCY OF TEACHING THE DIFFERENTIAL EQUATIONS MODULE IN TECHNICAL HIGHER EDUCATION INSTITUTIONS AND THE QUALITY OF EDUCATION (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Abstract. The article discusses the integration of students using traditional and software in solving problems in the teaching of the differential equations module taught in technical higher education institutions.